2009
DOI: 10.1152/japplphysiol.90368.2008
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular metabolism during low-intensity resistance exercise with blood flow restriction

Abstract: Although recent studies have reported that low-intensity resistance training with blood flow restriction could stress the muscle effectively and provide rapid muscle hypertrophy and strength gain equivalent to those of high-intensity resistance training, the exact mechanism and its generality have not yet been clarified. We investigated the intramuscular metabolism during low-intensity resistance exercise with blood flow restriction and compared it with that of high-intensity and low-intensity resistance exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
177
2
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(204 citation statements)
references
References 42 publications
6
177
2
19
Order By: Relevance
“…Numerous studies have found that the ischemic (88) and hypoxic (92) intramuscular environment associated with BFR protocols induces a greater rate of ATP hydrolysis, exaggerated PCr depletion (85) decreased pH (84,85), and an increased lactate response (26,74,76,88,89). Suga et al (84) found greater metabolic stress (i.e., PCr, Pi, and deprotonated phosphate) via 31P--magnetic resonance spectroscopy, during low--intensity exercise (20% of 1RM) with BFR (varying pressure; 18.5--cm cuff width) vs. lowintensity (20% of 1RM) without BFR. However, the degree of metabolic stress was significantly less vs. a higher intensity protocol without BFR (65% of 1RM).…”
Section: Metabolic Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have found that the ischemic (88) and hypoxic (92) intramuscular environment associated with BFR protocols induces a greater rate of ATP hydrolysis, exaggerated PCr depletion (85) decreased pH (84,85), and an increased lactate response (26,74,76,88,89). Suga et al (84) found greater metabolic stress (i.e., PCr, Pi, and deprotonated phosphate) via 31P--magnetic resonance spectroscopy, during low--intensity exercise (20% of 1RM) with BFR (varying pressure; 18.5--cm cuff width) vs. lowintensity (20% of 1RM) without BFR. However, the degree of metabolic stress was significantly less vs. a higher intensity protocol without BFR (65% of 1RM).…”
Section: Metabolic Responsesmentioning
confidence: 99%
“…However, the degree of metabolic stress was significantly less vs. a higher intensity protocol without BFR (65% of 1RM). However, it is also important to note that Suga et al (84) used a single set of repetitions to exhaustion. In separate research, Suga et al (85) examined the acute effects of multiple sets on intramuscular metabolic stress during 2 separate low--intensity plantar flexion exercise bouts (20% of 1RM; 3 sets of 30 repetitions; 1--minute rest intervals between) under 2 distinct BFR bouts (intermittent-pressure released during rest intervals between sets; continuous-pressure maintained throughout exercise and released after the final set); and a high--intensity bout (65% of 1RM; 3 sets of 30 repetitions; 1--minute rest intervals between sets) and a low--intensity bout (20% of 1RM; 3 sets of 30 repetitions per set; 1--minute rest intervals between sets), both without BFR.…”
Section: Metabolic Responsesmentioning
confidence: 99%
“…Metabolic stress results from the accumulation of metabolic by-products such as H + and Pi 18) . It has been hypothesized that the development of metabolic stress triggers secondary reactions including the recruitment of additional motor units to compensate for the force loss 19) , elevation of systemic hormones 20) , greater acute muscle cell swelling 21) and production of reactive oxygen species (ROS) 22) .…”
Section: Exercise Load and Muscle Hypertrophy In Resistance Trainingmentioning
confidence: 99%
“…Further, mechanical stress has been shown to directly stimulate cellular process responsible for hypertrophy (Miyazaki et al 2011;Vandenburgh and Kaufman 1979). The hypertrophic response has also been attributed to metabolic factors, given that blood flow restriction exercise at low intensities results in significant hypertrophy (Suga et al 2009). Takada et al (Takada et al 2012) also showed that both muscle cross-sectional area and strength were correlated with metabolic stress after a 4-week intervention.…”
Section: Introductionmentioning
confidence: 99%